2011
DOI: 10.1186/1476-7120-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Pre-ejection period by radial artery tonometry supplements echo doppler findings during biventricular pacemaker optimization

Abstract: BackgroundBiventricular (Biv) pacemaker echo optimization has been shown to improve cardiac output however is not routinely used due to its complexity. We investigated the role of a simple method involving computerized pre-ejection time (PEP) assessment by radial artery tonometry in guiding Biv pacemaker optimization.MethodsBlinded echo and radial artery tonometry were performed simultaneously in 37 patients, age 69.1 ± 12.8 years, left ventricular (LV) ejection fraction (EF) 33 ± 10%, during Biv pacemaker opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The vessel motion and blood flow with overlaid tissue elasticity, in response to a certain external pressure level, generate a unique pulsation in the RA, which is utilized for the diagnosis of various diseases by oriental clinicians [14]. Moreover, the RA is used to measure the central blood pressure by tonometry or a sphygmomanometer [15,16], and thus the RA was selected as the target vessel for HFUS in this study.…”
mentioning
confidence: 99%
“…The vessel motion and blood flow with overlaid tissue elasticity, in response to a certain external pressure level, generate a unique pulsation in the RA, which is utilized for the diagnosis of various diseases by oriental clinicians [14]. Moreover, the RA is used to measure the central blood pressure by tonometry or a sphygmomanometer [15,16], and thus the RA was selected as the target vessel for HFUS in this study.…”
mentioning
confidence: 99%
“…Recent data available in the literature also indicate that there is a significant reduction in radial tonometry measured PEP postoptimization compared to preoptimization values and that this reduction correlates with echo Doppler measured improvements in hemodynamics. Optimization also significantly reduced the PEP/ED ratio . Moreover, data available in literature supporting the use of RAT in evaluating CRT response are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Data available in the literature indicate that radial artery tonometry (RAT) showed a good correspondence with the echo‐Doppler‐derived cardiac parameters (i.e., longer LV ejection duration [ED]) in CRT patients . In addition, it was recently demonstrated that an acute pre‐ejection period (PEP) shortening measured by radial tonometry occurs with optimization of AV and VV delay and correlates with improvement in hemodynamics measured by echocardiography (Figure ). Whether the PEP, ED, and PEP/ED ratio are modified by MPP interventions compared to conventional CRT and whether radial tonometry, in conjunction with an ECG, can detect these changes has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in patients with CRT, optimizing atrioventricular (AV) delay further improves stroke volume [3-6] and that optimal AV delay changes over time requiring periodic optimization [7]. There is controversy on optimal AV delay at increase in heart rate with exercise.…”
mentioning
confidence: 99%